Implementasi Pendidikan Agama Islam Berbasis Kearifan Lokal Dalam Konteks Global - Jamaluddin Hanapi; Amaluddin Amaluddin (FKIP UNSULTRA, 2025)
Islamic Religious Education (PAI) has an important role in shaping the character and morals of students. In the midst of globalization that brings foreign cultural influences, the integration of local wisdom values ​​in the implementation of PAI is a strategic effort to maintain cultural identity and strengthen contextual Islamic values. This literature study aims to explore how the implementation of local wisdom-based PAI can contribute to strengthening religious and national identity in a global context. Through a review of various national and international journal sources in the last five years, it was found that the locality approach in PAI can have a positive influence on attitudes of tolerance, love of the homeland, and cultural resilience of students. This study also highlights the importance of synergy between universal Islamic values ​​and local traditions that are in line with Islamic principles. In the global era, this integration is important so that religious education is not separated from the cultural roots of society. The implications of this study indicate that educational institutions, teachers, and policy makers need to develop a PAI curriculum that is inclusive of local values ​​in order to create a generation of Muslims who are characterful, moderate, and adaptive to global dynamics.